Tom Clancy [compact disc, unabridged] : power and empire - Cameron, Marc (Random House Audio ; Books on Tape, 2017)
Jack Ryan is dealing with an aggresive challenge from the Chinese government. It seems that President Zhao is determined to limit Ryan's choices in the upcoming G20 negotiations. But there are hints that there's even more going on behind the scene. A routine traffic stop in rural Texas leads to a shocking discovery--a link to a Chinese spy who may have intelligence that lays bare an unexpected revelation. John Clark and the members of the Campus are in close pursuit, but can they get the information in time?